Transient receptor potential ankyrin 1 channel: An evolutionarily tuned thermosensor - Synytsya, Viktor; Vlachová, Viktorie (Physiological research, 2021)
The discovery of the role of the transient receptor potential ankyrin 1 (TRPA1) channel as a polymodal detector of cold and pain-producing stimuli almost two decades ago catalyzed the consequent identification of various vertebrate and invertebrate orthologues. In different species, the role of TRPA1 has been implicated in numerous physiological functions, indicating that the molecular structure of the channel exhibits evolutionary flexibility. Until very recently, information about the critical elements of the temperature-sensing molecular machinery of thermosensitive ion channels such as TRPA1 had lagged far behind information obtained from mutational and functional analysis. Current developments in single-particle cryo-electron microscopy are revealing precisely how the thermosensitive channels operate, how they might be targeted with drugs, and at which sites they can be critically regulated by membrane lipids. This means that it is now possible to resolve a huge number of very important pharmacological, biophysical and physiological questions in a way we have never had before. In this review, we aim at providing some of the recent knowledge on the molecular mechanisms underlying the temperature sensitivity of TRPA1. We also demonstrate how the search for differences in temperature and chemical sensitivity between human and mouse TRPA1 orthologues can be a useful approach to identifying important domains with a key role in channel activation.
Keywords: Animals; vnímání teploty; ankyriny; nízká teplota; lidé; vysoká teplota; Mice; Thermosensing; Hot Temperature; Humans; TRPA1 Cation Channel; kationtový kanál TRPA1; myši; Ankyrins; zvířata; Cold Temperature